Functional Outcomes, Operating Time, Bleeding Rate and Weight Bearing in Short Vs Long PFNA in IT Femur Fracture - Shoaib, Muhammad; Hussain, Asad Moiz; Muhammad Nadeem; Tareen, Najeeb; Khan, Ahmed Mushtaq; Yasin, Azhar (Indus Journal of Bioscience Research, 2024)
Objective: In order to manage intertrochanteric (IT) femur fractures, this study compares the functional outcomes, operating time, bleeding rate, and weight-bearing capability using short and long proximal femoral nail antirotation (PFNA). Methods: Patients who received PFNA for IT femur fractures between April and September of 2024 were the subjects of a retrospective investigation. Based on the length of the PFNA used, sixty patients were split into two groups: thirty received a short PFNA and thirty received a long PFNA. The time it took to reach full weight-bearing, operating time, intraoperative bleeding rate, and functional results as measured by the Harris Hip Score (HHS) at 6 and 12 weeks were among the important factors assessed. A statistical analysis was performed on the data to identify any noteworthy variations between the two groups. Results: There were 60 patients in the trial; 30 were in the long PFNA group and 30 were in the short PFNA group. The short PFNA group had an average operating duration of 45 minutes, which was considerably less than the long PFNA group’s 65 minutes (p<0.05). The short PFNA group experienced a considerably lower intraoperative blood loss (average of 140 ml) than the long PFNA group (average of 210 ml) (p<0.05). The HHS’s measure of functional outcomes showed no statistically significant difference in scores at 12 weeks (p=0.65) between the two groups. There was no discernible difference in the recovery period between the two groups’ average time to reach full weight-bearing, which was 8 weeks. The lengthy PFNA group had slightly fewer complications, such as fixation failure, but the difference was not statistically significant (p=0.58). Conclusion: Reduced operating time and less intraoperative bleeding are two benefits of short PFNA, without sacrificing weight-bearing ability or functional results. While both short and long PFNA offer comparable functional outcomes, addressing IT femur fractures may benefit more from short PFNA’s potential for greater effectiveness and safety. Additional investigation, including prospective studies, is important to corroborate these results and evaluate enduring consequences.